2022
DOI: 10.20411/pai.v7i1.499
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Soluble ST2 Levels are Associated With Neuronal Injury and Neurocognitive Impairment in Children With Cerebral Malaria

Abstract: Background: Murine experimental cerebral malaria studies suggest both protective and deleterious central nervous system effects from alterations in the interleukin-33 (IL-33)/ST2 pathway.  Methods: We assessed whether soluble ST2 (sST2) was associated with neuronal injury or cognitive impairment in a cohort of Ugandan children with cerebral malaria (CM, n=224) or severe malarial anemia (SMA, n=193).  Results: Plasma concentrations of sST2 were higher in children with CM than in children with SMA or in asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Furthermore, we observed an inverse correlation between anti-PF4/P IgG and circulating platelet count in Ret+ CM (Rs=-0.201, p=0.048; Supplemental Table S1, Figure 4A). (55)(56)(57). Anti-PF4/P antibodies have not been described in association with anemia, but we observed an inverse correlation in UM cases between anti-PF4/P and Hemoglobin (HgB: Rs=-0.225, p=0.015) and packed cell volume (PCV: Rs=-0.200, p=0.029) (Supplemental Table S1).…”
Section: Anti-pf4/p Antibodies Are Associated With Markers Of Thrombo...mentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, we observed an inverse correlation between anti-PF4/P IgG and circulating platelet count in Ret+ CM (Rs=-0.201, p=0.048; Supplemental Table S1, Figure 4A). (55)(56)(57). Anti-PF4/P antibodies have not been described in association with anemia, but we observed an inverse correlation in UM cases between anti-PF4/P and Hemoglobin (HgB: Rs=-0.225, p=0.015) and packed cell volume (PCV: Rs=-0.200, p=0.029) (Supplemental Table S1).…”
Section: Anti-pf4/p Antibodies Are Associated With Markers Of Thrombo...mentioning
confidence: 62%
“…ST2 levels are also positively associated with anti-PF4/P IgG levels and negatively associated with peripheral platelet count. ST2 is an interleukin-1-like receptor to the alarmin interleukin 33 (IL-33), associated with neuroinflammation and vascular dysfunction (68-70), and was recently described as a prognostic marker of neurological sequelae in children with CM (55).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of plasma sST2 levels were significantly associated with cognitive impairment in acute ischemic stroke patients [ 142 , 143 ]. Elevated plasma levels of sST2 may contribute to neuronal injury and long-term neurocognitive impairment in older children with cerebral malaria [ 144 ]. Its ability to bind two different isoforms of ST2 may at least partly account for the dual roles of IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, serum soluble ST2 (sST2) which is a receptor of interleukin-33 can play an important role in acting as a potential prognostic biomarker for TBI 11 . Nowadays, it has been found that sST2 are associated with neuronal injury and neurocognitive impairment in CM patient 12 .…”
Section: Correlations Between Cerebral Malaria and Traumatic Brain In...mentioning
confidence: 99%